PEDAGOGICAL STUDIES: THE CHALLENGES OF SANTRI IN BILINGUAL PROGRAMS - NA'IMAH, NA'IMAH; HAMID, ABDUL WARIS; SYAFRUDDIN, MUHAMMAD ANDI; WIDYAWATI, DEWI (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The era of globalization has required humans to utilize international language as a means of communication. Many educational institutions implement a bilingual program, such as the one implemented by MA SyaikhZainuddin NW Anjani. The purpose of this study is to analyze the challenges of students in the bilingual program. Data collection techniques in this study include observation, interviews, and documentation. Observations were used to observe the process of implementing the bilingual program at MA SyaikhZainuddin NW Anjani. Interviews were used to obtain information on the development of the bilingual program. The analysis in this study uses descriptive qualitative. The study results indicate that the challenge of students in the Bilingual program at MA SyaikhZainuddin NW Anjani begins with applying two languages. It is done by introducing what language is. After the introduction stage, the students are asked to memorize the vocabulary given, with the aim that students can interact using the two languages, but based on the results of research in the field, many students have difficulty memorizing vocabulary because of the density of the hours of this subject causes problems for students. However, the teachers motivate students to keep learning the language to facilitate learning.